1987
DOI: 10.2307/1590774
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcosis of Turkeys. 1. Portal of Entry and Tissue Colonization

Abstract: Staphylococcus aureus and various coagulase-negative staphylococci were isolated from turkeys with staphylococcosis. Virulent S. aureus adhered well (averaged more than 100 bacteria per tissue cell) in vitro to cells from tissues of the respiratory tract but did not adhere well (averaged fewer than 12 bacteria per tissue cell) to cells from tissues of the alimentary tract. Some avirulent coagulase-negative staphylococci also adhered well to cells from the respiratory tissues. Lungs and livers of turkeys became… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…Several subsequent attempts to reproduce BCO using S. aureus by aerosol in broilers also proved unsuccessful (Mutalib et al, 1983b), despite the additional stresses of wetting and chilling. Jensen et al (1987) found that the lung and liver of 19-day-old turkeys became colonized by S. aureus following aerosol exposure to this pathogen. They concluded that the presence of liver infection indicated passage of the bacteria from the respiratory tract into the blood or lymphatic system, although the exact mechanism of spread was not determined.…”
Section: Inoculation Of S Aureus Via Aerosolmentioning
confidence: 97%
See 1 more Smart Citation
“…Several subsequent attempts to reproduce BCO using S. aureus by aerosol in broilers also proved unsuccessful (Mutalib et al, 1983b), despite the additional stresses of wetting and chilling. Jensen et al (1987) found that the lung and liver of 19-day-old turkeys became colonized by S. aureus following aerosol exposure to this pathogen. They concluded that the presence of liver infection indicated passage of the bacteria from the respiratory tract into the blood or lymphatic system, although the exact mechanism of spread was not determined.…”
Section: Inoculation Of S Aureus Via Aerosolmentioning
confidence: 97%
“…However, although they were unable to demonstrate a relationship between the occurrence of osteomyelitis and stress under experimental conditions , Mutalib et al (1983a) suggested that stress might initiate outbreaks in chickens that have a latent staphylococcal colonization from an early age. Jensen et al (1987) suggested that staphylococcal infections did not result primarily from injection of the organism due to injury, insect bites or cuts to the skin, rather that the respiratory tract was the most likely portal of entry of S. aureus in poultry on the basis of preferential S. aureus adherence to cells of the respiratory tract compared with cells from other tissues. Such adhesion of S. aureus to the surface of the host cell has been shown to be important in bovine mastitis and endocarditis in humans (Foster, 1991), in human osteomyelitis (Ryden et al, 1989) and in osteomyelitis in chickens (Alderson & Nade, 1987).…”
Section: Pathogenesismentioning
confidence: 99%
“…A connection between virulence and adherence among bacterial species, including some staphylococcal strains, has been suggested. For example, in turkeys, strains of S. aureus with a high level of adherence to lung cells also expressed a high level of virulence 12 . Also, Cree & Noble 13 suggested that among S. intermedius , isolates from lesions of pyoderma in dogs may represent strains with increased adherence to damaged skin due to exposure of extracellular matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Mutalib et al (1983b) were unable to reproduce disease after exposing broiler chickens to 5. aureus aerosols. However Jensen et al (1987) demonstrated colonization of turkey lungs following aerosol exposure in vivo. In the present study, the role of the respiratory tract as a major route of infection seems unlikely since most birds were kept in open, uncrowded enclosures, and exposure to infected aerosols would have been minimal.…”
Section: Discussionmentioning
confidence: 99%